A technology review of recycling methods for fiber-reinforced thermosets. (June 2022) - Xue, Xiao; Liu, Shu-Yan; Zhang, Zhao-Yang; Wang, Qing-Zhou; Xiao, Cheng-Zhi
The rapidly rising demand for fiber-reinforced plastics (FRPs) has led to large volumes of manufacturing and end-of-life waste. Recycling fiber-reinforced thermosets is very difficult owing to their complex structure and heterogeneity. Landfill and incineration have become the most commonly used methods for eliminating non-degradable FRP waste, which adversely affects the environment and ecology. The purpose of this review is to evaluate end-of-life FRP recycling technologies in terms of optimizing the reuse/recycling of resources and eliminating waste, thereby improving FRP waste management. The technical progress made in the recycling of thermosetting composites is reviewed, including mechanical, thermal (pyrolysis and fluidized-bed), and chemical (critical fluid and low-temperature solvent) methods. The technical feasibility of each method was compared, and the economic and environmental impacts were considered. The challenges and opportunities facing the establishment of a composite recycling market in the future are examined. Finally, we provide a comprehensive summary of the scope of each recycling method.